Evaluation of Optical Efficiency of Circular Cross-Section Torus Waveguide via Changing the Optical Parameters - Abd Al-Majeed , Kawthar H.; Hasan, Alaa B.; Aldeen , Sameer H. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The efficiency of solar systems was developed through the design of a torus waveguide, which provides high flexibility in the design of the solar system. The design was simulated using the optical design program (ANSYS Zemax Optic Studio 2022). The circular cross-section torus waveguide was shaped like the letters (U, S) to transmit solar radiation through total internal reflection inside the waveguide to the receiver (solar cell or thermal reservoir). To improve the solar system's efficiency, a group of optical parameters related to the waveguide's shape were changed to demonstrate the effect of changing them on the system's performance. These parameters include the radius of curvature of the waveguide, the width of the entry apertures, and the angle of rotation. The results showed that the designed waveguide shapes offer high flexibility in size and shape without significantly affecting the system's efficiency. This flexibility allows for greater diversity in the design of solar systems, depending on their intended purpose.